COMPARATIVE ANALYSIS OF CONSONANTS IN ENGLISH AND UZBEK LANGUAGES - Sharipova Yorqinoy, (TADQIQOTLAR, 2025)
Abstract:  The  phonetic  and  phonological  systems  of  languages  play  a fundamental role in shaping spoken communication, and consonants constitute one of the  core  components  of  these  systems.  A  comparative  analysis  of  consonants  in different  languages  provides  valuable  insight  into  articulatory  mechanisms, phonological organization, and language-specific sound patterns. This article presents a comparative analysis of the consonant systems of the English and Uzbek languages with the aim of identifying their similarities, differences, and distinctive phonological features.  The  study  examines  consonants  from  both  articulatory  and  phonological perspectives, focusing on criteria such as place and manner of articulation, voicing, and phonemic  distribution.  Particular  attention  is  given  to  consonant  inventories, classification  principles,  and  the  functional  load  of  consonant  phonemes  in  both languages.  The  analysis  reveals  that  while  English  and  Uzbek  share  a  number  of common consonantal features, including plosives, fricatives, and nasals, they differ significantly in terms of the number of phonemes, the presence or absence of certain consonant types, and the role of secondary articulatory features. Special emphasis is placed on consonants that pose difficulties in second language acquisition, such as interdental fricatives in English and uvular or affricate sounds in Uzbek. The study also considers phonotactic constraints, allophonic variation, and the influence of consonant clusters  on  pronunciation  patterns.  These  differences  are  shown  to  reflect  broader typological  distinctions  between  the  two  languages,  as  well  as  their  historical  and phonological development.